Digitalisasi Pembelajaran Tafsir Al-Qur’an Dalam Meningkatkan Kualitas Pendidikan Agama Islam - Hasan Nurdin; Habibah Siti Masruuroh; Zaid Muhammad Firdan (PT. Pusmedia Group Indonesia, 2026)
This study aims to examine the use of digital technology in Qur’anic exegesis (tafsir) learning within Islamic Religious Education and its implications for improving learning quality. The research employs a qualitative approach using a library research method, which relies on various written sources as primary data, including books, scholarly journals, and relevant academic documents. Data collection was conducted through a systematic review of the literature by considering relevance, source credibility, and the recency of publications within the last five years. Data were analyzed using content analysis techniques to identify patterns, themes, and meanings from the reviewed literature. The findings indicate that digital technology plays a significant role in enhancing students’ understanding of Qur’anic tafsir. The utilization of digital platforms providing both classical and contemporary tafsir sources, along with interactive features such as visualization, gamification, and virtual reality, has been proven effective in enriching learning experiences, increasing student participation, and improving learning retention and motivation. Furthermore, the integration of digital technology contributes to transforming traditional learning models into more interactive and student-centered approaches. However, this study also identifies several challenges, including the digital divide and limited teacher competence in utilizing digital technologies. Therefore, strategic efforts are required, such as improving technological infrastructure and providing continuous professional development for teachers. The integration of digital technology should also be combined with contextual and in-depth learning approaches, such as direct discussions with scholars, to ensure a comprehensive understanding of tafsir. Overall, digital technology holds great potential to enhance the quality of tafsir learning, provided that its implementation is carried out appropriately and systematically.